Dinámica poblacional y reproductiva de Turbinella angulata y Busycon perversum (Mesogasteropoda: Turbinellidae y Melongenidae) en el Banco de Campeche, México - Santos Valencia, Josefina (2013)
Turbinella angulata and Busycon perversum are two marine gastropods that support the 90% of conch fisheries in the Gulf of Mexico, nevertheless there is no information available to support a management strategy for both species. The aim of this work was to obtain preliminary fishery information to promote management actions for both species in the Campeche Bank. The population of conchs was sampled in 12 transects (150x1.5m) by SCUBA diving from April 2008 to March 2010. All conchs were collected and siphonal length (SL) was measured. These samples were complemented with data from the commercial catches, analyzing a total of 2 832 individuals of T. angulata. Siphonal length varied between 63 and 282mm. Sex ratio was of 0.98:1 female:male. The von Bertalanffy growth equation parameters were: L∞=346mm; K=0.30 and t0=-0.24. Spawning extended from January to May with a long resting stage from June to September for over 80% of the adult population. The first gonadic maturity (L50) was at 210mm (SL) for females and 200mm for males. For B. perversum a total of 1 655 individuals were analyzed. Siphonal length varied between 78 and 291mm with significant differences between male and female (p<0.05). Sex ratio was of 1:0.25 female:male. The growth parameters obtained were: L∞=360mm; K=0.35 and t0=-0.19. The spawning period was from August to December with resting stage from January to April. The L50 was 215mm (LS) for females and 190mm for males. Both species presented one recruitment pulse. These results will be useful to design management schemes based on population dynamics and reproductive attributes.